Effects of Antenatal Body Mass Index on maternal and fetal outcome. - Chandraratne, S.M.P (My University, 2004)
This is a hospital based prospective cohort study with internal controls conducted at Castle street Hospital for women’s who attend antenatal clinic and receive inward treatment at ward 7 and 8.High BMI is associated with increased incidence of pregnancy induced hypertension (p0.01), diabetes mellitus (p0.01) urinary tract infections (p0.01),meconium stained liquor (p0.01)fetal distress/unfavorable cardiotocograph (p0.05), labour inductions (p0.01),undergoing caesarean sections (p0.01),mean birth weight (p0.01) Deep vein thrombosis 9p0.01) and increased admissions to baby unit (p0.01).High BMI is protective for occurrence of anaemia, IUGR and low birth weight. Low BMI is associated with increased occurrence of anaemia (p0.01),mean POA at delivery 38 weeks (p0.01) ,pre labour rupture of membrane (p0.01),spontaneous labour (p0.01),normal vaginal deliveries (p0.01) and lower mean birth weight (p0.01).Low protective against occurrence of PHI,DM,UTI,meconium stained liquor ,labour inductions caesarean sections and deep vein thrombosis. Deviation outside normal BMI range is associated with increased occurrence of wound infections episiotomy infections and admissions to special care baby unit. High and low is associated with adverse pregnancy outcome. Therefore need for preconception/ antenatal counseling and antenatal management